2021
DOI: 10.1186/s13662-021-03217-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling dynamics of fast food and obesity for evaluating the peer pressure effect and workout impact

Abstract: In recent years, chronic diseases, such as high blood pressure, diabetes, heart attack, and cancer, have increased around the world. Obesity is a common factor that makes individuals susceptible to these diseases. One reason for excessive weight gain is the frequent consumption of fast food. This study examined the impact that fast food has on obesity by analyzing the influence of peer pressure on fast food consumption and the role that exercise plays in weight gain. Two mathematical models were proposed to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Hence, we assume that atherosclerosis may spread through routine social interaction between infected individuals and susceptible individuals. This approach is common to model the spread of Noncommunicable diseases (NCDs) such as diabetes, cancer, and many more [12], [13], [14], [15]. The model differential equations are given below:…”
Section: The Mathematical Modelmentioning
confidence: 99%
“…Hence, we assume that atherosclerosis may spread through routine social interaction between infected individuals and susceptible individuals. This approach is common to model the spread of Noncommunicable diseases (NCDs) such as diabetes, cancer, and many more [12], [13], [14], [15]. The model differential equations are given below:…”
Section: The Mathematical Modelmentioning
confidence: 99%
“…Paudel [8] proposed a model for the dynamics of obesity with a SIR structure and analyzed the effect of the social network on the spread of obesity. Al-Tuwairqi and Matbouli [9] proposed two mathematical models to study the impact of fast food on the increase in obesity and the role of physical activity. Pietrus et al [10] developed a mathematical model to study the impact of media on the dynamics of obesity in a population.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [26] proposed a mathematical model to simulate the dynamic of social obesity by incorporating the structures of individual heterogeneity and overeating behaviors. Al-Tuwairqi and Matbouli [2] proposed two mathematical models to study the impact of fast food on obesity and the role that exercise plays in weight gain separately and showed that physical activity has a significant role in reducing weight. These works contributed to the construction of others models in particular, Bernard et al [6] developed a deterministic compartmental model for the dynamic of obesity and explored the impact of the media on the propagation of this phenomenon in a constant population.…”
Section: Introductionmentioning
confidence: 99%